How a perceived utilisation of IT-enabled information shapes customer satisfaction in B2B markets - Andreja Habjan (Business Systems Research (BSR), 2023)
Background: Despite the recognised benefits of IT, we still know very little about how the perceived utilisation of IT-enabled information by suppliers is linked to customer satisfaction in B2B markets. Objectives: To address this gap, this study develops a research model, which is then tested through a web-based survey of transport firms' customers. Methods/Approach: A web-based survey was conducted in Slovenia. The target population for this study was all export firms that utilise transport services. Results: The study makes two key contributions to B2B marketing literature. First, results show that the more a supplier is perceived to utilise IT-enabled information in the service process, the less emphasis its customers place on prices when it comes to determining their satisfaction. Second, the results suggest that customers view the utilisation of IT-enabled information by suppliers of B2B services as a value-adding capability that boosts service quality perceptions. Conclusions: Interestingly, although we expected that perceived utilisation of IT-enabled information would also increase the importance of service quality in forming customer satisfaction, the results suggested that this was not the case. Drawing on service quality literature, the study offers possible explanations.
Keywords: L11; 330; customer satisfaction; information technology; information utilisation; B2B; service quality; price